2013
DOI: 10.1159/000343221
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Anti-Interleukin-1 Therapy in Severe Hidradenitis Suppurativa: A Case Report

Abstract: Hidradenitis suppurativa (HS) is an inflammatory, debilitating skin disease of follicular origin, characterized by painful deep-seated, inflamed lesions in mainly the inverse areas of the body. HS is notoriously difficult to treat and especially severe disease is often resistant to therapy. New therapeutic options are therefore highly needed. Elevated levels of IL-1 have been demonstrated in HS lesions. Here we report for the first time on the sequential treatment with anakinra (an IL-1 receptor antagonist) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 18 publications
(20 reference statements)
0
37
0
2
Order By: Relevance
“…Several case studies support the use of anakinra in HS, although outcomes are variable. 35,36 Other groups have suggested that targeting IL-23/IL-12p40 may benefit HS. 37 TNF-a inhibitors are effective therapies for HS.…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies support the use of anakinra in HS, although outcomes are variable. 35,36 Other groups have suggested that targeting IL-23/IL-12p40 may benefit HS. 37 TNF-a inhibitors are effective therapies for HS.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine-mediated inflammation has been considered as immunosuppressive agents have been used. Blocking TNFα is effective in some patients but TNFα failures have been reported [144]. Elevated levels of TNFα as well as IL-1β are released from 24 h cultures of skin from these patients; the elevated levels are not only in lesional skin biopsies but also in the unaffected peripheral skin of the lesions [145].…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…The use and success of Anakinra for the treatment of HS has been a matter of controversy (van der Zee and Prens, 2013; Zarchi et al, 2013; Leslie et al, 2014; Menis et al, 2015; Russo and Alikhan, 2016). However, in a recent double-blind, randomized, placebo controlled trial, 20 patients were treated with Anakinra or placebo daily for 12 weeks.…”
Section: Skin Diseases With Il-1 Involvementmentioning
confidence: 99%